PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Sanjiwani, Ni Made Dwi; Suasana, I Gst. A. Kt. Gd. (E-Jurnal Manajemen; Vol 8 No 11 (2019)DO - 10.24843/EJMUNUD.2019.v08.i11.p17, 2019)
The purpose of this study is to examine the role of brand image in mediating the effect of product quality on purchasing decisions on Miniso products in Denpasar City. This research was conducted in the city of Denpasar by using a sample size of 100 people with a purposive sampling method. Data collection was obtained by the results of questionnaires using the measured Likert scale. The data analysis technique used in this study is path analysis technique, and is accompanied by a sobel test. The results of the study proposed that product quality had a significant effect on purchasing decisions on Miniso products, product quality had a significant effect on the brand image of Miniso products, brand image had a significant effect on purchasing decisions on Miniso products, and brand image was able to mediate the effect of product quality on purchasing decisions. product quality and imagery brand have a significant influence on purchasing decisions at the Miniso study program in Denpasar City. Keywords : brand image, product quality, purchasing decision